2003
DOI: 10.1021/ja029759w
|View full text |Cite
|
Sign up to set email alerts
|

Multivalency and the Mode of Action of Bacterial Sialidases

Abstract: Although complex modular proteins are encountered frequently in a variety of biological systems, their occurrence in biocatalysis has not been widely appreciated. Here, we describe that bacterial sialidases, which have both a catalytic and carbohydrate-binding domain, can hydrolyze polyvalent substrates with much greater catalytic efficiency than their monovalent counterparts. The enhancement of catalytic efficiency was due to a much smaller Michaelis constant and rationalized by a model in which the catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 17 publications
0
63
0
Order By: Relevance
“…[51][52][53][54] This particular bacterial neuraminidase was chosen because it (like human Neu1) preferentially removes terminal sialic acids from monovalent sialylated glycoproteins but not from sialylated gangliosides, as other bacterial sialidases do. We anticipated that the biological effects observed after treatment of cultured SMCs with the C. perfringens neuraminidase would differ from the effects recorded after treatment with Vibrio cholerae neuraminidase, [55][56][57] which preferentially hydrolyzes both Ϫ2,3-and Ϫ2,6-linked sialic acid residues from higher-order gangliosides.…”
Section: Cell Culturesmentioning
confidence: 99%
“…[51][52][53][54] This particular bacterial neuraminidase was chosen because it (like human Neu1) preferentially removes terminal sialic acids from monovalent sialylated glycoproteins but not from sialylated gangliosides, as other bacterial sialidases do. We anticipated that the biological effects observed after treatment of cultured SMCs with the C. perfringens neuraminidase would differ from the effects recorded after treatment with Vibrio cholerae neuraminidase, [55][56][57] which preferentially hydrolyzes both Ϫ2,3-and Ϫ2,6-linked sialic acid residues from higher-order gangliosides.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Like many glycosyl hydrolases, sialidases can possess carbohydrate-binding modules (CBMs) in addition to the catalytic domain, placed upstream, placed downstream, or even inserted within the ␤-propeller domain. It has been suggested that the presence of these CBMs increases the catalytic efficiency of the sialidases, particularly in the presence of polysaccharide substrates (25). In the case of sialidases having CBMs, they often recognize sialic acid as has been shown for the sialidases from Vibrio cholerae (26), Clostridium perfringens (27), and Streptococcus pneumoniae (15).…”
mentioning
confidence: 96%
“…Many sialidases possess domains in addition to the catalytic domain, placed upstream, downstream, or even inserted within the ␤-propeller domain; the Vibrio cholerae sialidase has two lectin domains flanking the catalytic domain, one of which binds sialic acid (18); Micromonospora viridifaciens sialidase has a galactose-binding domain C-terminal to the catalytic domain and is positioned above the active site (20); the leech sialidase has a lectin-like domain N-terminal to the catalytic domain (15), and the trypanosome (trans-) sialidases have a lectin-like domain C-terminal to the catalytic domain (13,14). It has been suggested that the presence of these carbohydratebinding modules increases the catalytic efficiency of the sialidases, particularly in the presence of polysaccharide substrates (21). Many glycoside hydrolases have additional carbohydratebinding modules, particularly those involved in the degradation of insoluble polysaccharides such as cellulose and starch, and these carbohydrate-binding modules show a great diversity in ligand recognition and folds (22).…”
mentioning
confidence: 99%